Learning to be Norwegian: a case study of identity management in religious education in Norway - Iversen, Lars Laird (Religious diversity and education in Europe, 2012)
Biographical note: Lars Laird Iversen works as associate professor at the Norwegian School of Theology, where he teaches social science. His research interests focus on the sociology of religion, education and national identity.